The Influence of Emotional Intelligence and Stress Management on Teacher Performance at Public Junior High School - Nurhasanah, Neni; Wijaya, Candra (EDUTEC : Journal of Education And Technology, 2024)
The purpose of this research is to determine: (1) The influence of emotional intelligence on the performance of teachers at State Junior High School 35 Percut Sei Tuan; (2) The influence of stress management on the performance of teachers at State Junior High School 35 Percut Sei Tuan; and (3) The combined influence of emotional intelligence and stress management on the performance of teachers at State Junior High School 35 Percut Sei Tuan. The population of this study is all teachers at State Junior High School 35 Percut Sei Tuan, totaling 56 people, with a sample size of 30 people. The research instrument is a questionnaire using the Likert scale model. Assumption tests were conducted to test for normality and linearity. Data analysis techniques used simple and multiple regression at a significance level of α = 0.05. The findings of this research indicate: (1) The influence of emotional intelligence (X1) on the performance of teachers at State Junior High School 35 Percut Sei Tuan (Y) is 94.2% with the equation Ῠ = 6.998 + 0.911 X1; (2) The influence of stress management (X2) on the performance of teachers at State Junior High School 35 Percut Sei Tuan (Y) is 98.2% with the regression equation Ῠ = 0.283 + 1.043 X2; and (3) The combined influence of emotional intelligence (X1) and stress management (X2) on the performance of teachers at State Junior High School 35 Percut Sei Tuan (Y) is 98.3% with the regression equation Ῠ = 1.223 + 0.148 X1 + 1.206 X2. This regression line equation explains that if emotional intelligence and stress management factors increase by one unit, teacher performance will also increase by 2.557 units.